2023
DOI: 10.21203/rs.3.rs-2620877/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relating community capacity to the adoption of an evidence-based prevention strategy: a community-level analysis

Abstract: Background: In community-based prevention, adopting an evidence-based strategy is known to predict prevention success. Evidence-based prevention includes a theoretical framework, empirical assessment of prevention needs, use of tested and effective prevention programs, monitoring of community prevention efforts and outcomes, and integration of practice experiences. Also known is that adopting evidence-based prevention requires community capacity. However, it is unclear which domains of community capacity are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In a previously conducted scoping review, we identified nine dimensions of community capacity that have most commonly been utilized in prior studies to measure capacity in the field of prevention and health promotion ( Birgel et al, 2023 , Birgel et al, 2023 ). Our study involves a secondary data analysis of a Community Key Informant Interview (CKI) from the CTC-EFF-Study.…”
Section: Introductionmentioning
confidence: 99%
“…In a previously conducted scoping review, we identified nine dimensions of community capacity that have most commonly been utilized in prior studies to measure capacity in the field of prevention and health promotion ( Birgel et al, 2023 , Birgel et al, 2023 ). Our study involves a secondary data analysis of a Community Key Informant Interview (CKI) from the CTC-EFF-Study.…”
Section: Introductionmentioning
confidence: 99%